Die Transformation der Informationsmärkte in Richtung Nutzungsfreiheit Alternativen zur Als-ob-Regulierung im Wissenschaftsurheberrecht - Kuhlen, Rainer (Age of Access? Grundfragen der Informationsgesellschaft, 2020)
In the last 30 years, copyright law's approach to knowledge and information has come under fire. This book makes an important contribution to the debate about the sustainability of current models combining freedom of use and public financing. The author proposes a concept of "rights of use and freedom of use for knowledge and information" to replace copyright law applying to individual cases.